A poesia de Ernani Fornari : recuperação e fixação de éditos e inéditos - Dall’alba, Julia Darol (2020)
This research has two general objectives: to recover the work of Ernani Fornari, as well as his intellectual and cultural history, and to fix his poetic work, updating it in order to disseminate and make it aware. The corpus comprises all of EF's poetry books and reaches about 200 poems: the published, Missal da ternura e da humildade (Livraria do Globo, 1st edition, 1923, and Livraria do Globo, 2nd edition, 1933), Trem da serra (Livraria do Globo, 1st edition, 1928 and Editora Acadêmica, 2nd edition, 1987), Praia dos milagres (Livraria do Globo, 1st edition, 1932), and the unpublished Praia dos milagres (2nd edition) and Quatro poemas brasileiros. As a methodological procedure, a comparison of the works will be carried out, the copy-text editing, supported by the procedures of textual criticism, the linguistic updating and the establishment of notes, introduced by brief presentations of the works, exposing their specificities, stories and aesthetic influences.